Hyperglycemia causes renal cell damage via CCN2-induced activation of the TrkA receptor: implications for diabetic nephropathy. - Fragiadaki, M; Hill, N; Hewitt, R; Bou-Gharios, G; Cook, T; Tam, F; Domin, J; Mason, R (2012)
CCN2, a secreted profibrotic protein, is highly expressed in diabetic nephropathy (DN) and implicated in its pathogenesis; however, the actions of CCN2 in DN remain elusive. We previously demonstrated that CCN2 triggers signaling via tropomyosin receptor kinase A (TrkA). Trace expression of TrkA is found in normal kidneys, but its expression is elevated in several nephropathies; yet its role in DN is unexplored. In this study we show de novo expression of TrkA in human and murine DN. We go on to study the molecular mechanisms leading to TrkA activation and show that it involves hypoxia, as demonstrated by ischemia-reperfusion injury and in vitro experiments mimicking hypoxia, implicating hypoxia as a common pathway leading to disease. We also expose renal cells to hyperglycemia, which led to TrkA phosphorylation in mesangial cells, tubular epithelial cells, and podocytes but not in glomerular endothelial cells and renal fibroblasts. In addition, we report that hyperglycemia caused an induction of phosphorylated extracellular signal-related kinase 1/2 and Snail1 that was abrogated by silencing of TrkA or CCN2 using small interfering RNA. In conclusion, we provide novel evidence that TrkA is activated in diabetic kidneys and suggest that anti-TrkA therapy may prove beneficial in DN.